(untitled) (Research, Society and Development, 2021)
Due to the social isolation caused by the COVID-19 pandemic, the performance of physical activities underwent necessary adaptations through digital platforms of interactive communication. For the practice to be possible, education professionals used resources to overcome the difficulties. The aim of this study is to show how physical education professionals acted during the COVID-19 pandemic and the tools and platforms used. The work has as specific objectives; a) to know the ways physical education professionals have found to obtain new results; b) to show how physical education professionals used digital platforms during this pandemic period; c) to check best to get results through the internet. This is a descriptive analysis, quantitative cross-sectional research, through the application of a questionnaire designed in-house. The research sample consisted of physical education professionals with full training or bachelor’s degree. The results obtained show that the use of the Internet was an effective way to maintain the frequency of training, thus helping to fight the COVID-19 pandemic. It is concluded that it is of fundamental importance that physical education professionals can reinvent themselves and overcome the challenges imposed by the market.